Personality Type and Religious Leadership - Oswald, Roy M.; Kroeger, Otto (Rowman & Littlefield Publishers, 1988)
Combining pastoral and behavioral science expertise, the authors spell out ways type and temperament theory illuminate the clergy role. Learn how to use the 16 Myers-Briggs personality types to recognize and affirm your gifts, work with your liabilities, and understand and accept those with whom you minister. "Being a parish pastor is a very complex role. Our mission in this book is to make that task a little less complex and a little more fun by looking at our congregations through the lens of the MBTI." -- The authors